Abnormal PTPN11 enhancer methylation promotes rheumatoid arthritis fibroblast-like synoviocyte aggressiveness and joint inflammation - Maeshima, Keisuke (JCI Insight, 2016)
The PTPN11 gene, encoding the tyrosine phosphatase SHP-2, is overexpressed in rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS) compared with osteoarthritis (OA) FLS and promotes RA FLS invasiveness. Here, we explored the molecular basis for PTPN11 overexpression in RA FLS and the role of SHP-2 in RA pathogenesis. Using computational methods, we identified a putative enhancer in PTPN11 intron 1, which contained a glucocorticoid receptor–binding (GR-binding) motif. This region displayed enhancer function in RA FLS and contained 2 hypermethylation sites in RA compared with OA FLS. RA FLS stimulation with the glucocorticoid dexamethasone induced GR binding to the enhancer and PTPN11 expression. Glucocorticoid responsiveness of PTPN11 was significantly higher in RA FLS than OA FLS and required the differentially methylated CpGs for full enhancer function. SHP-2 expression was enriched in the RA synovial lining, and heterozygous Ptpn11 deletion in radioresistant or innate immune cells attenuated K/BxN serum transfer arthritis in mice. Treatment with SHP-2 inhibitor 11a-1 reduced RA FLS migration and responsiveness to TNF and IL-1β stimulation and reduced arthritis severity in mice. Our findings demonstrate how abnormal epigenetic regulation of a pathogenic gene determines FLS behavior and demonstrate that targeting SHP-2 or the SHP-2 pathway could be a therapeutic strategy for RA.